Architectural transitional justice?: Political renewal within the scars of a violent past - Mihai, Mihaela (International journal of transitional justice, 2018)
Located at the intersection of political theory, memory studies and architecture, this article tentatively proposes the concept of architectural transitional justice (TJ) to capture architecture’s power to provide favourable spaces for two interrelated processes: grappling with a violent past while simultaneously imagining a hopeful future. It argues that architecture can support - though not ensure - political renewal. While TJ scholars have explored architecture’s part in memorialization, they have mostly focused on symbolic constructions. This article shifts focus and examines a broader category of buildings that were integral to the geography of violence but whose function was not primarily symbolic. Such buildings scar the architectural tissue of successor political orders. The article crosses disciplinary boundaries to understand how communities can valorize these scars, avoiding both nostalgic and tabula rasa approaches to reconstruction. The reinvention of two Nazi Flak towers in Vienna and Hamburg serves as a potential instantiation of architectural TJ.